Potensi Aliran Permukaan dan Sedimentasi pada Drainase Alami Permukiman Pengungsi Erupsi Gunung Sinabung di Siosar, Kabupaten Karo - Nius Abdi Ginting; Rauf Rauf; Delvian Delvian (Fakultas Teknik, 2022)
Transformation from forest ecosystem to be residential and farming ecosystems generally causes changes and damages due to open land surface and groundwater run off which can decrease organic substances in that area. The research employs a survey method by comparing Watershed with forest, part of forest, and part of settlement as land covering and settlement with topographic boundaries in order to estimate the potency of groundwater run off surface. Primary data are collected by measuring discharge in field and measuring the parameter of water quality. Secondary data are collected from geographical position, history of Siosar forest, digital RBI map, meteorological data, and population statistic data. The result of research shows that deforestation for settlement increases water discharge of surface runoff and sedimentation especially in the rainy season. The quality of water in the forest area is relatively good whereas the quality of water in settlement is slightly polluted.